PERILAKU ISOTERM SORPSI AIR DAN DAN PERUBAHAN FISIK KERUPUK TAPIOKA PADA SUHU PENYIMPANAN YANG BERBEDA - Novriaman Pakpahan; Feri Kusnandar; Elvira Syamsir (Jurnal Teknologi dan Industri Pangan, 2017)
The qualities of tapioca crackers after frying, such as degree of expansion and crispness are influenced by their moisture content before frying. This research aimed to study the moisture sorption isotherm (MSI) behavior of crackers at different storage temperatures and their physical properties before and after frying. Pre-fried crackers were stored at water activities (aw) of 0.07-0.89 and 20, 30, and 40°C and their MSI pattern as well as bound water were determined, while their physical changes were observed. The fittest MSI model was Guggenheim, Anderson and de Boer (GAB). The primary bound water at 20, 30 and 40°C were 0.043, 0.040, dan 0.037 g H2O/g solid, while the secondary bound water were 0.096, 0.102, and 0.113 g H2O/g solid, respectively. The density and texture profile of the pre-fried crackers changed rapidly above their secondary bound water. Rapid reduction in the degree of expansion and crispness occurred at tertiary bound water. The aw of pre-fried crackers with high degree of expansion were at 0.33-0.53, 0.42-0.57, and 0.53-0.63 when stored at 20, 30, and 40°C, respectively. At the same storage conditions their maximum degree of expansion occurred at aw of 0.44, 0.47, and 0.52, respectively. Similarly, high crispiness occurred at aw of 0.33-0.57, 0.42-0.57, and 0.40-0.63, respectively, while maximum cripsness was at aw of 0.44, 0.44, and 0.54, respectively.